Narrating Nature : Wildlife Conservation and Maasai Ways of Knowing - Goldman, Mara (Critical green engagements., 2020)
""Narrating Nature opens up dialogue that counters traditional conservation narratives. It offers conservation efforts that not only include people as beneficiaries, but demonstrates how they are essential and knowledgeable members of the conservation landscape itself"--Provided by publisher"--